Slope stabilization influenced by unsaturated soil - Muhammad Farhan, Zolkepli (2018)
This study provides the exploration of methods for slope stabilization influenced by unsaturated soil. Two methods known as Bishop's Simplified method and also Fellenius's method are use in order to determine the factor of safety (FOS) of unsaturated soil slope. Since these methods were only applicable to determine the FOS value of saturated soil slope only, some modifications need to be done. The original formula of Bishop's Simplified method will be modified by adding the elements of matric suction, (µa-µw) and unsaturated friction angle øb so that it is applicable to calculate slope stability of unsaturated soil slope. Fellenius's method was already modified by previous researcher. The research employed several approaches i.e sample collection, laboratory experimental and slope analysis. The soil sample was collected at Pahang Matriculation College involving disturbed and undisturbed samples. The laboratory works were conducted to determine both index properties and engineering properties of soil. From the analysis, the soil at Pahang Matriculation College can be considered as Sandy SILT with high plasticity. From the result of engineering properties, the cohesion value is 9 kPa, the saturated friction angle ø' is 25º and the unsaturated friction angle øb 21º. The slope analysis to design the slope measurement was conducted using SLOPE/W. The FOS calculation involved both Bishop's and Fellenius's methods. The FOS values were determined from SLOPE/W first, and then using manual calculation to make sure there was only little percentage of difference of FOS value when calculating using both software and manual calculation. Finally, the FOS values for unsaturated soil slope for both methods were compared to determine which method gave higher FOS value with and without suction. From the result of analysis, it can be concluded that, the FOS value for both saturated and unsaturated soil slope is much higher when calculated using Bishop‟s Simplified method compare to Fellenius's method.